1987
DOI: 10.3109/00365528708991496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omeprazole on Gastric Mucosal Blood Flow in the Conscious Rat

Abstract: Regional blood flow in the gastrointestinal tract (forestomach, corpus, antrum, duodenum, jejunum, and colon) was determined in the conscious rat by means of the microsphere technique. The effects on blood flow were determined after omeprazole (orally and intravenously) and cimetidine (intravenously) during both basal and pentagastrin-stimulated gastric acid secretion. Under basal conditions neither omeprazole nor cimetidine decreased the blood flow in the gastrointestinal tract in spite of pronounced inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…As expected, the increase in GMBF response induced by histamine was closely associated with acid secretion; this response was almost completely attenuated when acid secretion was inhibited by cimetidine. These results are in agreement with findings of Mattsson and Larsson (1987), Kato et al (1993), and Pique et al (1992). It has been reported that enhanced acid secretion is induced by histamine in histidine decarboxylase (HDC)‐deficient mice.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, the increase in GMBF response induced by histamine was closely associated with acid secretion; this response was almost completely attenuated when acid secretion was inhibited by cimetidine. These results are in agreement with findings of Mattsson and Larsson (1987), Kato et al (1993), and Pique et al (1992). It has been reported that enhanced acid secretion is induced by histamine in histidine decarboxylase (HDC)‐deficient mice.…”
Section: Discussionsupporting
confidence: 93%
“…Variations in the transport rate of gastrin between the antral and corpus regions exert the strongest effect on acid levels (PRC coefficient ϭ 0.80, P Ͻ Ͻ 0.001). This is not unexpected given evidence for increased mucosal blood flow during feeding (49,69,79). We suggest that increasing blood flow increases the availability of gastrin in the corpus, thereby enhancing acid release.…”
Section: Importance Of Neural-independent Parameterssupporting
confidence: 61%
“…Previous investigations showed that om eprazole did not significantly affect gastric prostaglandin synthesis [5,24], bicarbonate secretion [10], or mucosal blood flow [11,12]. A possible involvement of gastric mucus barrier has been hypothesized [8], but not yet dem onstrated.…”
Section: Correlation Analysismentioning
confidence: 99%
“…In addition, omeprazole was shown not to significantly affect bicarbonate secretion [10] or gastric mucosal blood flow [11,12].…”
Section: Introductionmentioning
confidence: 99%